The Role of Muslim Entrepreneurs in Increasing the Welfare of the Sidoarjo Society - Hajar, Siti; Fauziah, Nur Dinah; A'yuni, Diah Syifaul (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
Ngingas Village is one of the villages that has a metal industrial center and is commonly referred to as a metal village. Ngingas Village itself is located in Waru District, Sidoarjo Regency, East Java Province. This village is neighboring Pandean Village which was formerly the originator of the metal industry. Ngingas became lively because metal production was varied and more in demand. Indeed, the Pandean area itself is a well-known metal-producing productive area in Sidoarjo. Even at a glance, people will not know that Pandean Village and Ngingas Village have the same special industrial center. Ngingas Village is a small, densely populated village whose majority of the population embraces Islam and has the same livelihood, namely working in the home metal industry, so it needs to be explored more deeply, which is research whose data is obtained from the actual location. While the method used is descriptive qualitative, namely the data obtained are presented in the form of interviews, documentation, and triangulation and then described so as to provide clarity.